Collective Security at the Crossroads - Abigail Georgison (Politikon)
On the 80th anniversary of the United Nations (UN), this paper revisits Andrea Charron’s 2007 discussion of the UN’s collective security framework in “Expanding the UN’s Collective Security System.” Charron analyzed the UN’s capacity to uphold international peace and security, reviewing the Responsibility to Protect (R2P) and the Duty to Prevent as potential tools for strengthening collective security. This paper situates Charron’s work in the geopolitical landscape of 2007 and examines the R2P and Duty to Prevent doctrines against the seven ideal elements of security. It then analyzes the application of R2P in Libya in 2011 to evaluate its impacts and limitations with consideration of the seven ideal elements of security. Charron’s assertions and predictions are assessed within the contemporary geopolitical context of 2025. Finally, the paper reflects on the future of collective security and the challenges posed by an eroding international rules-based system.